2006
DOI: 10.1530/rep.1.01051
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between proliferating and apoptotic hormone-producing and endothelial cells in the equine corpus luteum

Abstract: The temporal relationship between endothelial cell death, vascular regression and the death of hormone-producing cells in the mare has not been established. To determine the dynamics of cell proliferation and death throughout the luteal phase, corpora lutea were studied at the early, mid-and late luteal phase, and after treatment with cloprostenol in the mid-luteal phase to induce premature luteolysis. Changes in cell proliferation and apoptosis were investigated utilising specific markers (phosphorylated hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…In addition, death of hormone-producing and endothelial cells was consistently observed to occur contemporaneously. Similarly, in humans, the peak level of cell death in the corpus luteum is apparent during the peri-menstrual period, with no evidence of this being preceded by preferential endothelial cell loss (Gaytan et al 1998, Morales et al 2000, while in the regressing equine corpus luteum, we have found that activated caspase-3 staining appears simultaneously in the hormone-producing and the endothelial cells (Aguilar et al 2006). These and other observations (Funayama et al 1996) indicate that structural luteolysis normally follows functional luteolysis in the primate, and there is as yet no convincing evidence to show that during this process, endothelial cells die before hormone-producing cells.…”
Section: Discussionmentioning
confidence: 42%
“…In addition, death of hormone-producing and endothelial cells was consistently observed to occur contemporaneously. Similarly, in humans, the peak level of cell death in the corpus luteum is apparent during the peri-menstrual period, with no evidence of this being preceded by preferential endothelial cell loss (Gaytan et al 1998, Morales et al 2000, while in the regressing equine corpus luteum, we have found that activated caspase-3 staining appears simultaneously in the hormone-producing and the endothelial cells (Aguilar et al 2006). These and other observations (Funayama et al 1996) indicate that structural luteolysis normally follows functional luteolysis in the primate, and there is as yet no convincing evidence to show that during this process, endothelial cells die before hormone-producing cells.…”
Section: Discussionmentioning
confidence: 42%
“…Active caspase-3 was also identified in large luteal cells and endothelial cells [74, 78]. In both steroidogenic and endothelial cells, the increase in caspase-3 expression was on day 14 of the luteal phase or 36 h after PGF2 α administration [89]. Another important finding is the relationship between the onset of caspase-3 expression in endothelial cells on day 14 of luteal phase (or after luteolysis induction) and the decrease in mRNA and protein expression of VEGF in steroidogenic cells [81].…”
Section: Vascular Regulation In the Equine Corpus Luteummentioning
confidence: 99%
“…The complex development of a vascular network from a primitive endothelial sprout involves apoptotic death of endothelial cells during lumen formation and vascular remodelling (Lienau et al., 2005; Watson, Grant, & Coultas, 2017). Analysis of equine endothelial apoptosis can be successfully done via TUNEL test detecting DNA fragmentation (Al‐zi'abi, Fraser, & Watson, 2002) or via activated caspase‐3, another marker for apoptosis (Aguilar et al., 2006).…”
Section: Equine Endothelial Cells and Angiogenesis (Heterogeneity Mamentioning
confidence: 99%
“…Angiogenic activity was monitored by different methods. Measurements of vascular perfusion (Abdelnaby & El‐Maaty, 2017), capillary density (Ferreira‐Dias, Bravo, Mateus, Redmer, & Medeiros, 2006; Ferreira‐Dias & Mateus, 2003; Watson & Ai‐zi'abi, 2002), proliferation and apoptosis in situ (Aguilar et al., 2006) as well as evaluation of angiogenesis assays in vitro (Ferreira‐Dias, Costa, et al, 2006) show an increase in angiogenesis before ovulation and in the early and mid‐luteal phase in the equine ovary.…”
Section: Angiogenesis Research In Equine Reproductionmentioning
confidence: 99%